STATE REGULATION OF AGRIBUSINESS UNDER CONDITIONS OF EUROPEAN INTEGRATION - Tkachenko, Serhii (Public Management and Policy, 2025)
The article explores the mechanisms of state regulation of Ukraine’s agribusiness sector in the context of European integration, particularly in terms of adapting to the requirements of the European Union’s Common Agricultural Policy. The purpose of the article is to analyze the specific features of state regulation in Ukraine’s agricultural sector under European integration and to identify directions for its adaptation to the requirements of the EU’s Common Agricultural Policy. The study employed general scientific methods of cognition: analysis and synthesis; induction and deduction; a systems approach; comparative legal analysis; the historical-logical method; as well as modeling. The results show that Ukraine views the integration of its agricultural sector with the EU as a strategic development vector focused on increasing the competitiveness of agricultural production, gaining access to EU financial instruments, and building a sustainable agricultural development model. The article examines the key principles underlying the functioning of the EU’s Common Agricultural Policy, which operates through a system of decentralized administration, financial equalization, environmental regulation, and support for small and medium-sized farms. It is shown that agricultural policy in the EU is financed through the EAGF and EAFRD, with oversight ensured by the Integrated Administration and Control System (IACS), which covers the majority of agricultural budget expenditures. The study reveals that Ukraine’s agricultural policy is currently undergoing deep transformation: harmonization with EU legislation has been strengthened, land reform has been accelerated, and instruments of state support have been improved. Strategic challenges are highlighted, including the raw material orientation of exports and disparities in access to land and financial resources. The potential of cooperative movements and the development of family farming are outlined as essential conditions for ensuring social stability in rural areas. The practical value of the study lies in identifying strategic priorities for Ukraine’s state agricultural policy in the context of integration into the common European market.